High precision global positioning system data processing velocity vector determination for geodynamic application - Abu Bakar, Rabieahtul (2006)
Geodynamic studies involving Malaysia have been ventured upon in the South-East Asia region since the first GeodySEA project was carried out in 1996. For the fact that both East and West Malaysia lies on the same plate, we can assume that there will be no linear distortion for any two points joined relative to one another. In other words, for GPS observations over MASS stations, the baselines formed relative to any other MASS station can be roughly assumed to be constant without any significant changes. Though presumably Malaysia is out danger, but we take it for granted that it lies within the buffer of the ‘Ring of Fire’. We are situated near several active faults lines. This study will only look upon three years of MASS data from which most of the data were available simultaneously processed with 3 consecutive years of selected IGS. Since this movement is not evident for short observation or even observation of 1-year time span, therefore, a longer period of observation is needed to identify this movement. In this research the author will output the relative MASS stations coordinates and velocity estimates in ITRF2000. At present the measures of quality for GPS derived coordinates given by commercial software packages tend to be unrealistic because unmodelled errors remain unaccounted for (Brown et al., 2002). In addition, commercial software packages are either over-optimistic, or conversely, are overly conservative and therefore have low fidelity (Keenan and Cross, 2001, Barnes et. al., 1998, Wang, 1999). However, in this study Bernese high precision GPS processing software version 4.2 is utilised to determine the final solution for the relative MASS station coordinates. Screening cycle slips, using linear combination of phase observables to estimate the site specific atmospheric parameters, and resolving ambiguities give a reliable coordinate of lesser than 10mm in horizontal and 15mm in vertical in predefined ITRF2000 frame